Los procesos cognitivos básicos de atención y memoria y la comprensión lectora en estudiantes de primer ciclo de la carrera de Ingeniería Agrícola de la Facultad Agropecuaria y de Recursos Naturales Renovables de la Universidad Nacional de Loja, 2024 - Benites Caigua, María José (2024)
The goal of this research was to analyze the relationship between the levels of the cognitive processes of attention and memory and reading comprehension in first cycle students of the Agricultural Engineering degree. The investigation had a quantitative, descriptive, correlational and transversal approach, with a non-experimental design. To evaluate the cognitive processes, the d2 test was used for attention, the memory subscale of the RIAS test and the ICLAU for reading comprehension, it was applied to the sample of 29 students. For the statistical analysis, the SPSS program was used, as well as Kendall's Tau-b, for interpretation the Pearson linear correlation coefficient interpretation table was handled. With Regard to the results obtained, the cognitive processes of attention and memory are at a medium level, likewise the students' reading comprehension reaches a medium level. For establishing the correlation between the variables, Kendall's Tau-b was used, getting values of 340 and 351 in attention and memory respectively, positioning in a range of medium magnitude referring to the correlation with reading comprehension. Concluding that there is a correlation between both study variables, therefore, the research hypothesis is accepted, which mentions that "The basic cognitive processes of attention and memory are significantly related to reading comprehension in the first-cycle students of the Agricultural Engineering degree”.